A Different Learning Way For Pupils With Specific Learning Disabilities - Benmarrakchi, FatimaEzzahra; El Kafi, Jamal; EL Hore, Ali (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Several factors may contribute to a child’s failure to learn, some possible causes of school failure are specific learning disabilities. Dyslexia is one of the most common learning disabilities; dyslexia is to fail to learn to read in spite of adequate environment, normal intelligence, and decent educational opportunities. Various studies have recently focused on dyslexia on different scientific areas. Our main focus was to explore the use of Information and Communication Technology (ICT) in education to improve learning for pupils with learning disabilities. In this paper we present a positive approach which considers dyslexia as a different learning style rather than a disability.